2021
DOI: 10.1109/lwc.2021.3071059
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Analysis of IRS-Based UAV Communications With Imperfect Phase Compensation

Abstract: This paper presents the capacity analysis of unmanned aerial vehicles (UAVs) communications supported by flying intelligent reflecting surfaces (IRSs). In the considered system, some of the UAVs are equipped with an IRS panel that applies certain phase-shifts to the incident waves before being reflected to the receiving UAV. In contrast to existing work, this letter considers the effect of imperfect phase knowledge on the system capacity, where the phase error is modeled as a von Mises random variable with par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 19 publications
1
68
0
Order By: Relevance
“…RIS carried by UAV approach has been proven to improve the performance of the system significantly in nonorthogonal multiple access (NOMA) [8], orthogonal frequency division multiple access (OFDMA) [9] VOLUME xxxx, xxxx and free-space optical (FSO) communication system [10]. The capacity and signal gain after applying the RIS-UAV system has been studied in [11], [12]. In [11], the RIS can be equipped with UAVs to apply certain phase shifts of the incident waves before it is reflected to the receiving UAV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RIS carried by UAV approach has been proven to improve the performance of the system significantly in nonorthogonal multiple access (NOMA) [8], orthogonal frequency division multiple access (OFDMA) [9] VOLUME xxxx, xxxx and free-space optical (FSO) communication system [10]. The capacity and signal gain after applying the RIS-UAV system has been studied in [11], [12]. In [11], the RIS can be equipped with UAVs to apply certain phase shifts of the incident waves before it is reflected to the receiving UAV.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity and signal gain after applying the RIS-UAV system has been studied in [11], [12]. In [11], the RIS can be equipped with UAVs to apply certain phase shifts of the incident waves before it is reflected to the receiving UAV. It can also be deployed on building walls to reflect radio waves towards specific UAVs in order to improve their received signal gain and enhance the performance of UAVs cellular communications [13].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, the reflected signals from each IRS element should be added coherently by adjusting the phase of each IRS element. Most of the work in the literature demonstrates that increasing the number of reflecting elements improves the signal quality with perfect phase estimation and compensation [2], or when all reflectors have equal phase errors statistics [3], [4]. However, when the statistical properties of the phase error for reflectors are not identical, then increasing the number of reflecting elements does not necessarily improve the link quality.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bit error rate (BER) and outage probability expressions have been derived in the presence of phase errors for a single user IRS under different channel models including LoS [3] and Nakagami-m fading [9]. The achievable capacity for IRS assisted UAV communications under LoS assumption is analyzed in [4]. The impact of the phase quantization errors on the achievable capacity is discussed in [5] where it is shown that phase quantization and phase noise can severely degrade the achievable rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation